Place memory and dementia: Findings from participatory film-making in long-term social care. (July 2015) - Capstick, Andrea; Ludwin, Katherine
Abstract: A participatory film-making study carried out in long-term social care with 10 people with Alzheimer-type dementia found that places the participants had known early in life were spontaneously foregrounded. Participants' memories of such places were well-preserved, particularly when photo-elicitation techniques, using visual images as prompts, were employed. Consistent with previous work on the 'reminiscence bump' in dementia, the foregrounded memories belonged in all cases to the period of life between approximately 5 and 30 years. Frequently the remembered places were connected with major life events which continued to have a strong emotional component. The continuing significance of place in the context of long-term dementia care is considered from a psychogeographical perspective. Highlights: Given free choice people in long-term dementia care chose to make films about their early lives. Participants spontaneously recalled a variety of external geographical locations. Places associated with emotionally charged events in the past were foregrounded. Key themes were freedom and escape, historical trauma, and overcoming adversity.